(untitled) (International Seven Journal of Health Research, 2023)
On December 31, 2019, cases of pneumonia of unknown etiology began to appear in the city of Wuhan, China, associated with a wholesale seafood market that traded live animal species. In January 2020, the World Health Organization (WHO) declared Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) a public health emergency of global concern. The majority of those infected with SARS-CoV-2 have developed mild symptoms, such as dry cough, digeusia, and fever. However, a small proportion of the affected individuals presented a severe clinical picture, which led to systemic complications and caused many patients to die. Besides systemic symptoms, changes in the oral tissues have been clinically observed, such as taste disorders, non-specific oral ulcerations, desquamative gingivitis, petechiae, and co-infections, among others. Recent studies indicate that the oral mucosa may be the target of the virus, from the observation of the distribution of angiotensin-converting enzyme 2 (ACE2) in its epithelial cells. From this premise, the oral cavity may play an active role in the pathogenesis of the novel coronavirus. This article, of descriptive nature, aims to report the cases of alterations in the buccal tissues associated with COVID-19, present in the literature, through searches performed on the Pubmed portal.